Update on the efficacy, effectiveness and safety of artemether–lumefantrine combination therapy for treatment of uncomplicated malaria - Pauline Byakika-Kibwika; Mohammed Lamorde; Harriet Mayanja-Kizza; et al (Dove Medical Press, 2009)
Pauline Byakika-Kibwika1,2, Mohammed Lamorde1,2, Harriet Mayanja-Kizza1, Concepta Merry1,2, Bob Colebunders3,4, Jean-Pierre Van geertruyden4,51Infectious Diseases Institute and Infectious Diseases Network for Treatment and Research in Africa (INTERACT), Faculty of Medicine, Makerere University, Kampala Uganda; 2Trinity College Dublin, Ireland; 3Dienst Clinical Sciences, Instituut voor Tropische Geneeskunde, Antwerp, Belgium; 4International Health, Epidemiology en Social Medicine, Universiteit Antwerpen, Antwerp, Belgium; 5Epidemiology Unit, Dienst Parasitologie, Instituut voor Tropische Geneeskunde, Antwerp, BelgiumAbstract: Artemether–lumefantrine is one of the artemisisnin-based combination therapies recommended for treatment of uncomplicated falciparum malaria. The drug combination is highly efficacious against sensitive and multidrug resistant falciparum malaria. It offers the advantage of rapid clearance of parasites by artemether and the slower elimination of residual parasites by lumefantrine. The combination can be used in all populations except pregnant mothers in the first trimester where safety is still uncertain. There are still concerns about safety and pharmacokinetics of the drug combination in children, especially infants, pregnant mothers and drug interactions with mainly non-nucleoside reverse transcriptase inhibitors and protease inhibitors used for HIV therapy.Keywords: artemether–lumefantrine, efficacy, effectiveness, safety, malaria